2012
DOI: 10.1021/bi300489s
|View full text |Cite
|
Sign up to set email alerts
|

Heme Binding Constricts the Conformational Dynamics of the Cytochrome b559′ Heme Binding Cavity

Abstract: Cytochrome b(559)' is a transmembrane protein formed by homodimerization of the 44-residue PsbF polypeptide and noncovalent binding of a heme cofactor. The PsbF polypeptide can dimerize in the absence and presence of heme. To monitor structural alterations associated with binding of heme to the apo-cytochrome, we analyzed the apo- and holo-cytochrome structure by electron paramagnetic resonance spectroscopy. Spin labeling of amino acids located close to the heme binding domain of the cytochrome revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…First, the polypeptides enter the membrane matrix; second, an α-helix interacts with and recognizes another α-helix at the conserved glycine and phenylalanine residues near the thylakoid lumen surface to make a (α/β) heterodimer; and third, the heme group is incorporated to coordinate the two histidines and form a mature holoprotein. According to our data and other results (Volkmer et al 2006); Ackdogan et al 2012), the heme group seems not to be necessary for the incorporation, recognition and stable assembly of the protein complex subunits. The consecutively maturation steps would be as the following:…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…First, the polypeptides enter the membrane matrix; second, an α-helix interacts with and recognizes another α-helix at the conserved glycine and phenylalanine residues near the thylakoid lumen surface to make a (α/β) heterodimer; and third, the heme group is incorporated to coordinate the two histidines and form a mature holoprotein. According to our data and other results (Volkmer et al 2006); Ackdogan et al 2012), the heme group seems not to be necessary for the incorporation, recognition and stable assembly of the protein complex subunits. The consecutively maturation steps would be as the following:…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, our data suggest that the photosynthetic natural Cyt b 559 assembly and maturation would most probably occur by a three step model as demonstrated for the (β/β) homodimer in (Volkmer et al 2006;Ackdogan et al 2012). First, the polypeptides enter the membrane matrix; second, an α-helix interacts with and recognizes another α-helix at the conserved glycine and phenylalanine residues near the thylakoid lumen surface to make a (α/β) heterodimer; and third, the heme group is incorporated to coordinate the two histidines and form a mature holoprotein.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, this technique is useful for studying metal complexes, inorganic and organic radicals, protein structures, drug delivery and surface defects, etc. [7][8][9][10][11][12][13]. Spin labeling of polystyrene (PS) in combination with EPR technique allows us to monitor the surface of nanobeads in solution [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…b 6 [ 8 , 28 32 ] or cyt. b 559 [ 9 , 33 37 ] have indicated that the respective holo-cytochromes spontaneously assemble in vitro and in vivo in presence of heme. The two b-type hemes of in vitro reconstituted cyt.…”
Section: Introductionmentioning
confidence: 99%